Propagating Surface Plasmon Polaritons on Systems with Variable Periodicity and Variable Gap-Depth - O’Toole, Silas (Materials (Basel), 2020)
Here we report on both simulations and experimental results on propagation and transmission of Surface Plasmon Polaritons (SPPs) through tunable gaps which were initially motivated by excitation of SPPs on a periodic arrangement of nanowires with mechanically tuneable periodicity. The general ability to vary the two-dimensional lattice constant results in an additional degree of freedom, permitting excitation of SPP’s for any combination of wavelength and angle of incidence within the tuning range of the system. Fabrication of the tunable system includes a transition from a continuously metal coated surface to small metal ribbons which can be separated from each other as a result of mechanical strain applied to the flexible PDMS substrate. This also results in the creation of tuneable gaps between the metal ribbons and variations in the thickness of the metal coatings. In order to explain the propagation of SPPs through such gaps we have employed Finite Difference Time Domain (FDTD) simulations of SPPs through model systems which contain gaps with varying depths and metal fillings.